Sample preparation for scanning Kelvin probe microscopy studies on cross sections of organic solar cells - Scherer, Michael; Saive, Rebecca; Daume, Dominik; Kröger, Michael; Kowalsky, Wolfgang (AIP Advances, 2013)
We prepared cross sections of P3HT:PCBM bulk heterojunction (BHJ) organic solar cells (OSCs) for the characterization of their potential distribution with scanning Kelvin probe microscopy. We compared results of samples obtained by microtome cutting of OSCs on plastic substrates, cleaving of OSCs on glass substrates, and milling with a focused ion beam. Their potential distributions were in good agreement with each other. Under short circuit conditions, potential gradients were detected in vicinity of the electrode/organics interfaces, with negligible electric fields within the bulk. We contacted the OSCs in a defined manner and studied their potential distribution under operating conditions.
Gesehen am 07.02.2022